The marginal propensity to hire - Davide Melcangi (Federal Reserve Bank of New York, 2018)
This paper studies the link between firm-level financial constraints and employment decisions, as well as the implications for the propagation of aggregate shocks. I exploit the idea that, when the financial constraint binds, a firm adjusts its employment in response to cash flow shocks. I identify such shocks from changes to business rates, a U.K. tax based on a periodically estimated value of the property occupied by the firm. A 2010 revaluation implied that similar firms, occupying similar properties in narrowly defined geographical locations, experienced different tax changes, allowing me to control for confounding shocks to local demand. I find that, on average, for every 1 of additional cash flow, 39 pence are spent on employment. I label this response the marginal propensity to hire (MPH). I then calibrate a firm dynamics model with financial frictions toward this empirical evidence. As in the data, small and leveraged firms in the model have a greater MPH. Simulating a tightening of credit conditions, I find that the model can account for much of the decline in U.K. aggregate output and employment observed in the wake of the financial crisis.
Keywords: E24; E44; G01; G32; 330; financial frictions; employment; heterogeneous firms